Comparative Genomics Sheds Light on the Convergent Evolution of Miniaturized Wasps. (13th September 2021) - Xu, Hongxing; Ye, Xinhai; Yang, Yajun; Yang, Yi; Sun, Yu H; Mei, Yang; Xiong, Shijiao; He, Kang; Xu, Le; Fang, Qi; Li, Fei; Ye, Gongyin; et al.
Abstract: Miniaturization has occurred in many animal lineages, including insects and vertebrates, as a widespread trend during animal evolution. Among Hymenoptera, miniaturization has taken place in some parasitoid wasp lineages independently, and may have contributed to the diversity of species. However, the genomic basis of miniaturization is little understood. Diverged approximately 200 Ma, Telenomus wasps (Platygastroidea) and Trichogramma wasps (Chalcidoidea) have both evolved to a highly reduced body size independently, representing a paradigmatic example of convergent evolution. Here, we report a high-quality chromosomal genome of Telenomus remus, a promising candidate for controlling Spodoptera frugiperda, a notorious pest that has recently caused severe crop damage. The T. remus genome (129 Mb) is characterized by a low density of repetitive sequence and a reduction of intron length, resulting in the shrinkage of genome size. We show that hundreds of genes evolved faster in two miniaturized parasitoids Trichogramma pretiosum and T. remus . Among them, 38 genes exhibit extremely accelerated evolutionary rates in these miniaturized wasps, possessing diverse functions in eye and wing development as well as cell size control. These genes also highlight potential roles in body size regulation. In sum, our analyses uncover a set of genes with accelerated evolutionary rates in Tri. pretiosum and T. remus, which might be responsible for their convergent adaptations to miniaturization, and thus expand our understanding on the evolutionary basis of miniaturization. Additionally, the genome of T. remus represents the first genome resource of superfamily Platygastroidea, and will facilitate future studies of Hymenoptera evolution and pest control.